COMPARATIVE ASSESSMENT OF THE PERFORMANCE OF ECONOMIC SYSTEMS BY SUSTAINABLE DEVELOPMENT INDICATORS (Marketing Journal, 2025)
The article highlights the theoretical and methodological approaches to comparing and evaluating the efficiency of economic systems based on sustainable № 10-SON OKTA BR, 2025 -YIL 215 development indicators. It reveals the essence of sustainable development as an integrated indicator that encompasses economic, social, and environmental components. The analysis of growth models characteristic of market, mixed, and transitional economic s ystems has been conducted. The main focus is placed on comparing indicators such as gross domestic product, human development index, energy consumption coefficient, share of “green” investments, and institutional quality index.
Keywords: sustainable development; economic system; performance; macroeconomic indicators; institutional factors; green economy; human capital; ecological efficiency